An experiment on the effect of psychic distance on internationalisation of retailers. (2017) - Szylit, Flavia; Botelho, Delane
One influential factor in internationalisation strategy, from export to own subsidiaries, is psychic distance, constituted here by cultural and business distances. Many studies have analysed the relationship between internationalisation strategy and psychic distance, however most empirical studies thus far have analysed the strategy a posteriori . We investigate whether psychic distance impacts both the aggressiveness of entry strategy and adaptation/standardisation of the marketing mix elements in the retail industry, in a manipulated environment setting in an emerging market, which allows us to explain a priori the possible motives that lead respondents to determine their strategic decisions. Our results evidence that the business distance influences both the aggressiveness of the entry strategy and the adaptation of the marketing strategy, and that cultural distance influences the adaptation of the marketing strategy. We provide insights for practitioners and academics according to the international marketing literature.